The Effect of Hybrid Work System and Multiple Role Conflict on Employee Performance - Simanullang Arly Aprilita; Ribhan Ribhan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The advancement of technology within organizations supports companies in innovating their work systems more efficiently and effectively. Technological sophistication has transformed the organizational work environment by enabling hybrid models that combine remote and in-office work. This research aims to examine the influence of hybrid work arrangements and dual role conflict on employee performance in Indonesia’s pharmaceutical sector. Data were gathered through a questionnaire distributed via Google Forms to 185 employees working in the pharmaceutical industry across Indonesia. The data analysis was conducted using SPSS version 27. The research instruments were tested for validity and reliability; validity was assessed through Confirmatory Factor Analysis (CFA MSA), including Kaiser-Meyer-Olkin (KMO), Anti-Image, and Factor Loadings. Normality was examined using the one-sample Kolmogorov-Smirnov test. Hypothesis testing employed multiple linear regression and t-tests. The findings indicate that both hybrid work systems and dual role conflict have a positive and significant impact on employee performance.